Amphetamine decorated cationic lipid nanoparticles cross the blood–brain barrier: therapeutic promise for combating glioblastoma. Issue 19 (24th April 2020) - Saha, Soumen; Yakati, Venu; Shankar, Gajji; Jaggarapu, Madan Mohan Chandra Sekhar; Moku, Gopikrishna; Madhusudana, Kuncha; Banerjee, Rajkumar; Ramkrishna, Sistla; Srinivas, Ragampeta; Chaudhuri, Arabinda
Abstract : BBB-crossing amphetamine decorated cationic lipid nanoparticle co-loaded with paclitaxel and PDL-1 siRNA enhances survivability of orthotopic glioblastoma bearing mice. Abstract : Combating brain tumors (glioblastoma multiforme or GBM) is a formidable challenge because of the existence of blood–brain barrier (BBB), a tight cellular junction that separates the central nervous system (CNS) and systemic circulation. Such a selectively permeable barrier prevents the entry of therapeutic molecules from blood circulation to brain parenchyma. Towards enhancing the efficacy of brain tumor-selective drug delivery without perturbing the BBB integrity, nanometric drug carriers are increasingly becoming an efficient therapeutic modality in preclinical studies. Psychostimulant drugs such as amphetamine and methylated amphetamine (METH) are known to penetrate the BBB. Still, little effort has been made to exploit them in nano-drug delivery, largely due to their toxicities. Herein, for the first time, we design, synthesize, and formulate three different β-amphetaminylated cationic lipid nanoparticles. We show that the β-amphetaminylated cationic lipid nanoparticles are nontoxic and can cross the BBB presumably through active transcytosis. The BBB penetrating ability also depends on the hydrophilic–hydrophobic balance of the lipids, with hexadecyl lipid (16-BACL) nanoparticle showing maximum accumulation in the brain. The lipid nanoparticle of 16-BACL can simultaneously encapsulate paclitaxel and PDL1-siRNA. The dual drug-loaded lipid nanoparticles showed apoptosis driven cellular cytotoxicity against GL261 cells and improved the overall survivability of orthotopic glioblastoma bearing mice compared to their non-targeting counterpart. The present work describes a new class of BBB-crossing lipid nanoparticles and delineates their therapeutic promise against glioblastoma.